2015
DOI: 10.1159/000369007
|View full text |Cite
|
Sign up to set email alerts
|

Additive Neuroprotection of a 20-HETE Inhibitor with Delayed Therapeutic Hypothermia after Hypoxia-Ischemia in Neonatal Piglets

Abstract: The severity of perinatal hypoxia-ischemia and the delay in initiating therapeutic hypothermia limit the efficacy of hypothermia. After hypoxia-ischemia in neonatal piglets, the arachidonic acid metabolite 20-hydroxyeicosatetraenoic acid (20-HETE) has been found to contribute to oxidative stress at 3 h of reoxygenation and to eventual neurodegeneration. We tested whether early administration of a 20-HETE synthesis inhibitor after reoxygenation augments neuroprotection with 3-hour delayed hypothermia. In two hy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
35
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 38 publications
(37 citation statements)
references
References 46 publications
(77 reference statements)
2
35
0
Order By: Relevance
“…In addition, the induction of the Cyp4a12a isoform, which is the primary enzyme responsible for formation of 20-HETE in the mouse, may contribute to the increase in 20-HETE production at this time. Previous studies have indicated that 20-HETE promotes increases in oxidative stress in ischemic brains (Zhu et al 2015; Yang et al 2012). Thus, the large increase in 20-HETE production at 3 h likely contributes to the ongoing neuronal cell death from that point forward.…”
Section: Discussionmentioning
confidence: 95%
“…In addition, the induction of the Cyp4a12a isoform, which is the primary enzyme responsible for formation of 20-HETE in the mouse, may contribute to the increase in 20-HETE production at this time. Previous studies have indicated that 20-HETE promotes increases in oxidative stress in ischemic brains (Zhu et al 2015; Yang et al 2012). Thus, the large increase in 20-HETE production at 3 h likely contributes to the ongoing neuronal cell death from that point forward.…”
Section: Discussionmentioning
confidence: 95%
“…Hypothermia confers neuroprotection in our piglet HI model by preserving viable neurons and reducing NMDA receptor activation, nitric oxide synthase relocalization, oxidative stress, and cellular necrosis. [32-35] However, hypothermia may promote apoptosis in cortex after HI [4] and in white matter with or without HI [5], which may reflect an off-target effect of hypothermia and rewarming.…”
Section: Discussionmentioning
confidence: 99%
“…[49] Rewarming reinitiates protein translation through dephosphorylation of eIF2-α in mammalian cells recovering from cold shock. [36] Upregulated protein translation with the accumulation of misfolded proteins in addition to cellular stressors from hypothermia with rewarming, such as inflammation [50] and oxidative stress, [35, 51, 52] may activate the UPR. [53, 54]…”
Section: Discussionmentioning
confidence: 99%
“…All of these cells types therefore have the necessary machinery to produce 19- and 20-HETE (Alonso-Galicia et al, 1999; Bylund et al, 2002; Al-Anizy et al, 2006; Gebremedhin et al, 1998; 2000; 2016; Carver et al, 2014, Dunn et al, 2008; Zhu et al, 2015; Zhang et al, 2017c). 20-HETE, but not 19-HETE have been detected in vascular smooth muscle cells, and more recently astrocytes and neurons (Gebremedhin et al, 1998; 2008; 2016; Zhang et al, 2017c).…”
Section: Distribution Of P450 Eicosanoids and Their Synthetic Enzymesmentioning
confidence: 99%